A phospholipid complex to improve the oral bioavailability of flavonoids. (3rd October 2015) - Wang, Huizhen; Cui, Yuqing; Fu, Qingxue; Deng, Bing; Li, Guowen; Yang, Jun; Wu, Tao; Xie, Yan
Abstract: Aim : A phospholipid complex (TFH-PC) was prepared to increase the oral bioavailability of isorhamnetin, kaempferol, and quercetin from TFH (total flavones of Hippophae rhamnoides L.). Methods : Solvent evaporation was used to prepare TFH-PC. Relevant parameters were investigated based on the complexation rate of isorhamnetin, kaempferol, and quercetin. Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), X-ray power diffraction (X-RPD), and scanning electron microscopy (SEM) were used for characterization. Solubility, octanol–water partition coefficient (log P ), dissolution rate, and in vivo pharmacokinetics were also investigated. Results : TFH-PC was successfully prepared in tetrahydrofuran with a drug to phospholipid ratio of 1:1, reaction temperature of 20 °C, and a reaction time of 1 h. The complexation rates of isorhamnetin, kaempferol, and quercetin were 97.7%, 95.97%, and 92.23%, respectively. FT-IR, DSC, X-RPD, and SEM confirmed the formation of TFH-PC. The aqueous solubilities of the three flavonoids in TFH-PC increased 22.0–26.8-fold compared with TFH. The dissolution of isorhamnetin, kaempferol, and quercetin in TFH-PC was 84.32%, 90.77%, and 100% within 10 min, respectively, greatly improved over TFH. After oral administration of TFH-PC in rats, the bioavailability of isorhamnetin, kaempferol, and quercetin in TFH-PC relative to TFH was 223%, 172%, and 242%, respectively. Conclusion : The oral absorption of isorhamnetin, kaempferol, and quercetin was significantly improved in TFH-PC, mainly due to increased solubility and dissolution rate. This phospholipid complex shows potential for oral delivery of the flavonoids in TFH.